2022
DOI: 10.1161/circgen.121.003589
|View full text |Cite
|
Sign up to set email alerts
|

Provocation Testing and Therapeutic Response in a Newly Described Channelopathy: RyR2 Calcium Release Deficiency Syndrome

Abstract: Background: A novel familial arrhythmia syndrome, RyR2 calcium release deficiency syndrome (CRDS), has recently been described. We evaluated a large and well characterized family to assess provocation testing, risk factor stratification and response to therapy in CRDS. Methods: We present a family with multiple unheralded sudden cardiac deaths and aborted cardiac arrests, primarily in children and young adults, with no clear phenotype on standard clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 31 publications
0
30
0
Order By: Relevance
“…They should perhaps be considered a separate familial RyR2-dependent, noncatecholaminergic arrhythmic syndrome. Indeed, many LOF mutants linked to sudden cardiac death or aborted cardiac death do not respond to exercise stress testing or produce the characteristic bidirectional ventricular tachycardia, hallmarks of CPVT ( Sun et al, 2021 ; Zhong et al, 2021 ; Ormerod et al, 2021 ). Instead LOF mutations lead to a CRDS, in which the general effect of the mutations on RyR2 is to reduce or abolish CICR indicated in [ 3 H] ryanodine binding and single channel experiments ( Zhao et al, 2015a ; Zhao et al, 2015b ; Jiang et al, 2007 ; Hirose et al, 2021 ).…”
Section: Flecainide’s Efficacy In Arrhythmogenic Lof Ryr2 Mutationsmentioning
confidence: 99%
See 2 more Smart Citations
“…They should perhaps be considered a separate familial RyR2-dependent, noncatecholaminergic arrhythmic syndrome. Indeed, many LOF mutants linked to sudden cardiac death or aborted cardiac death do not respond to exercise stress testing or produce the characteristic bidirectional ventricular tachycardia, hallmarks of CPVT ( Sun et al, 2021 ; Zhong et al, 2021 ; Ormerod et al, 2021 ). Instead LOF mutations lead to a CRDS, in which the general effect of the mutations on RyR2 is to reduce or abolish CICR indicated in [ 3 H] ryanodine binding and single channel experiments ( Zhao et al, 2015a ; Zhao et al, 2015b ; Jiang et al, 2007 ; Hirose et al, 2021 ).…”
Section: Flecainide’s Efficacy In Arrhythmogenic Lof Ryr2 Mutationsmentioning
confidence: 99%
“…At the cellular level, cells expressing these mutations lack detectable Ca 2+ oscillations and display a reduced sensitivity to caffeine and store-overload–induced Ca 2+ release (SOICR), suggesting they may not respond as fully to β-adrenergic stimulation ( Ormerod et al, 2021 ; Sun et al, 2021 ; Hirose et al, 2021 ; Zhao et al, 2015b ; Fujii et al, 2017 ). SR Ca 2+ content may be increased because of the lack of SOICR.…”
Section: Flecainide’s Efficacy In Arrhythmogenic Lof Ryr2 Mutationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is logical to infer that flecainide might exacerbate the CRDS phenotype if it can inhibit RyR2. To date, flecainide has proven to be a promising therapeutic agent for CRDS ( Tester et al, 2020 ; Ormerod et al, 2021 ). The programmed electrical stimulation protocol with a pattern of long-burst, long-pause, and short-coupled (LBLPS) can induce ventricular arrhythmias in transgenic mice with RyR2 LOF mutations.…”
Section: Flecainide Treatment In Calcium-release Deficiency Syndromementioning
confidence: 99%
“…In the induced pluripotent stem cell cardiomyocytes carrying homozygous RYR2 duplication, which presented LOF, Tester et al (2020) reported that flecainide significantly reduced arrhythmic activity caused by isopropanol. Ormerod et al (2021) tested flecainide in nine CRDS patients and found that the administration of flecainide substantially reduced arrhythmia inducibility in one subject and abolished arrhythmia in all others. Sun et al (2021) proposed that the therapeutic mechanisms of flecainide in CRDS are attributable to its multiple blocking of membrane channels.…”
Section: Flecainide Treatment In Calcium-release Deficiency Syndromementioning
confidence: 99%